2017
DOI: 10.1007/978-3-319-53047-5_14
|View full text |Cite
|
Sign up to set email alerts
|

The Tubulin Superfamily in Archaea

Abstract: In comparison with bacteria and eukaryotes, the large and diverse group of microorganisms known as archaea possess a great diversity of cytoskeletal proteins, including members of the tubulin superfamily. Many species contain FtsZ, CetZ and even possible tubulins; however, some major taxonomic groups do not contain any member of the tubulin superfamily. Studies using the model archaeon, Halferax volcanii have recently been instrumental in defining the fundamental roles of FtsZ and CetZ in archaeal cell divisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 69 publications
2
35
0
Order By: Relevance
“…Biochemistry and Immuno-fluorescence microscopy studies indicated that archaeal FtsZ proteins are GTPases and localized to the mid-cell plane of division, much like their bacterial counterpart [30][31][32]35]. Whereas most bacterial species studied so far contain only one FtsZ, many archaea are now known to carry two FtsZ homologues, one from each of two distinct sub-families, with FtsZ1 being apparently more closely related to bacterial and plant FtsZ, with FtsZ2 being more phylogenetically distinct [5,6,36]. The early studies had identified only the FtsZ1 homolog but not the FtsZ2 homolog that was also present in the archaea chosen for study [32,35].…”
Section: Ftsz Family Proteins In Archaeamentioning
confidence: 99%
See 4 more Smart Citations
“…Biochemistry and Immuno-fluorescence microscopy studies indicated that archaeal FtsZ proteins are GTPases and localized to the mid-cell plane of division, much like their bacterial counterpart [30][31][32]35]. Whereas most bacterial species studied so far contain only one FtsZ, many archaea are now known to carry two FtsZ homologues, one from each of two distinct sub-families, with FtsZ1 being apparently more closely related to bacterial and plant FtsZ, with FtsZ2 being more phylogenetically distinct [5,6,36]. The early studies had identified only the FtsZ1 homolog but not the FtsZ2 homolog that was also present in the archaea chosen for study [32,35].…”
Section: Ftsz Family Proteins In Archaeamentioning
confidence: 99%
“…The early studies had identified only the FtsZ1 homolog but not the FtsZ2 homolog that was also present in the archaea chosen for study [32,35]. One exception was the FtsZ2 homologue studied in H. salinarum [6,30], which appeared to cause altered cell morphology after its overexpression in H. salinarum [30].…”
Section: Ftsz Family Proteins In Archaeamentioning
confidence: 99%
See 3 more Smart Citations